2019
DOI: 10.1021/acs.macromol.9b01904
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Efficient Field-Theoretic Simulations for Block Copolymer Melts

Abstract: Field-theoretic simulations (FTS) provide fluctuation corrections to self-consistent field theory (SCFT) by simulating its field-theoretic Hamiltonian rather than applying the saddle-point approximation. Although FTS work well for ultrahigh molecular weights, they have struggled with experimentally relevant values. Here, we consider FTS for two-component (i.e., AB-type) melts, where the composition field fluctuates but the saddle-point approximation is still applied to the pressure field that enforces incompre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…A Markov sequence of configurations for the partition function in Equation ( 26 ) is generated by evolving the composition field, , using Langevin dynamics, where thermal noise is provided by random numbers, , generated from a normal distribution of zero mean and variance. To improve accuracy, we apply the predictor-corrector algorithm [ 47 , 48 ]. A predicted field at is first obtained using Equation ( 36 ) with and then a corrected field is obtained with evaluated using the predicted field and corresponding composition.…”
Section: Field-theoretic Simulationsmentioning
confidence: 99%
See 3 more Smart Citations
“…A Markov sequence of configurations for the partition function in Equation ( 26 ) is generated by evolving the composition field, , using Langevin dynamics, where thermal noise is provided by random numbers, , generated from a normal distribution of zero mean and variance. To improve accuracy, we apply the predictor-corrector algorithm [ 47 , 48 ]. A predicted field at is first obtained using Equation ( 36 ) with and then a corrected field is obtained with evaluated using the predicted field and corresponding composition.…”
Section: Field-theoretic Simulationsmentioning
confidence: 99%
“…In the Morse calibration, the nonlinear correction is calculated by fitting the peak of the structure function, , from FTS to ROL predictions for symmetric diblocks. Beardsley and Matsen [ 13 , 48 ] demonstrated the calibration for and , assuming the empirical relationship [ 4 ] between the bare of the FTS and the effective of the ROL theory. The resulting calibration, , , and , is plotted in the inset of Figure 2 .…”
Section: Field-theoretic Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…By adapting the FTS to a variety of different ensembles, they found evidence for A þ B þ BμE coexistence, but the high computational costs limited the size of their simulations boxes and resulted in significant metastability issues. Since then, however, Beardsley et al [46] found a speedup of about two orders of magnitude by switching to conventional Langevin simulations. With this improvement in hand, we revisit the ternary blends.…”
mentioning
confidence: 99%